The Reuse of Classical Antiquity in the Palace of Madinat al-Zahraʾ and Its Role in the Construction of Caliphal Legitimacy - Capilla, Susana Calvo (Muqarnas, 2014)
The appearance of a group of Roman statues and sarcophagi in different buildings of the palace of Madinat al-Zahra⁠ʾ founded by Caliph ʿAbd al-Rahman III (r. 912–61) raises several questions about the revival of classical antiquity promoted by the caliphal court of Cordoba in the tenth century. The pieces—reused as basins for water fountains—had hitherto been considered irrelevant to the architectural and historical study of the caliphal palace, even though their discovery and location in specific buildings of the complex are essential to understanding and determining the function of these spaces. In addition, this discovery will help to interpret the range of the cultural development of the caliphal court and its relevance in the construction of political theory in al-Andalus in the tenth century. In this article I first examine the intellectual context in which these pieces were displayed, which lets us understand the reasons these particular characters—heroes, philosophers, and Muses—and scenes were chosen. I also consider the relationship these pieces had with their designated locations and to what extent their existence might suggest that these were spaces related to scientific and intellectual activities.